2018
DOI: 10.3168/jds.2018-15034
|View full text |Cite
|
Sign up to set email alerts
|

Ketoprofen affects the mammary immune response in dairy cows in vivo and in vitro

Abstract: Nonsteroidal anti-inflammatory drugs are commonly administered parenterally in addition to antimicrobial mastitis therapy to increase the well-being of the diseased animal. As mastitis is usually a localized infection of mammary tissue, we tested the hypothesis that a local administration of nonsteroidal anti-inflammatory drugs through the teat canal could have anti-inflammatory effects on the affected area. We investigated the effects of intramammarily administered ketoprofen (KET) during an LPS-induced immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 33 publications
4
15
2
Order By: Relevance
“…Results of the present study show that the addition of MEL to bovine MEC diminishes the processes of inflammation not only at the mRNA level but also at the protein level. In contrast to our results, Dan et al (2018) did not find any change in the synthesis of PGE 2 using similar doses (1.25 and 2.5 mg/mL) of ketoprofen in addition to LPS-challenged MEC, letting us conclude that the selectivity and type of NSAID are essential for this response.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Results of the present study show that the addition of MEL to bovine MEC diminishes the processes of inflammation not only at the mRNA level but also at the protein level. In contrast to our results, Dan et al (2018) did not find any change in the synthesis of PGE 2 using similar doses (1.25 and 2.5 mg/mL) of ketoprofen in addition to LPS-challenged MEC, letting us conclude that the selectivity and type of NSAID are essential for this response.…”
Section: Discussioncontrasting
confidence: 99%
“…When cells received 1.5 mg/mL MEL in addition to the PAMP, the mRNA abundance of most cytokines was similar to nontreated controls at all time points. Even if more attenuate, Dan et al (2018) found similar results in mRNA abundance of TNF and IL-8 of MEC treated with 0.2 µg/mL LPS in combination with 1.25 or 2.5 mg/mL ketoprofen, a non-selective NSAID. In an inflamed mammary gland it could be interesting to decrease the exacerbated production of leukocyte chemoattractants by MEL because it is known that excessive neutrophil infiltration leads to production of reactive oxygen species, tissue destruction, and mortality (Kolaczkowska and Kubes, 2013).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…On the one hand, antioxidants protect immune cells from oxidative stress, making them more successful in eliminating pathogens (Sordilllo, ) and thus leading to lower SCC. On the other hand, it is known from recent studies that non‐steroidal anti‐inflammatory drugs (NSAID) are able to reduce SCC during and after acute or induced mastitis (Dan, Bruckmaier, & Wellnitz, ; McDougall, Bryan, & Tiddy, ). These findings may indicate that overshooting immune reactions of the mammary gland could be counterproductive for the restorative process of the mammary gland after an inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…Because ketoprofen is characterized by a rapid onset of action, a short plasma half-life, low toxicity (Kantor, 1986), and no need for milk withdrawal after treatment, it could be justified for clinical mastitis therapy. Although some studies have evaluated the efficacy of ketoprofen for clinical mastitis treatment (Shpigel et al, 1994;Banting et al, 2008;Dan et al, 2018), outcomes such as risk of clinical and microbiological cure and relapse and recurrence of clinical mastitis have not been studied. To our knowledge, the efficacy of ketoprofen to treat culture-negative clinical mastitis cases following OFC results has not been studied.…”
Section: Introductionmentioning
confidence: 99%